Improvement of BGP Session Maintenance - Amin, Sadia; Ahthasham, Saira; Shaikh, Aftab Ahmed; Sajid, Ahthasham; Mehmood, Mirza Aamir (International Journal of Engineering and Technology, 2012)
In the early days, the Internet used static routes, but very quickly network administrators couldn’t keep manually updating their routing tables. Later, Internet network administrator used a protocol called EGP but EGP was not scalable so BGP was introduced to solve all problems and more. BGP stands for Border Gateway Protocol and the most current version is BGP4. BGP is a routing protocol that runs on routers. BGP allows fully decentralized management of the Internet. That means, if BGP router is on the Internet, it can tell all other routers that what networks are available to everyone in the world. BGP calls each routing domain an autonomous system (AS). It selects the best path, through the Internet, by choosing the route that has to traverse the fewest autonomous systems. As BGP provides information for controlling the flow of packets between ASes, the protocol plays a critical role in Internet efficiency, reliability, and security. However, slow convergence and abnormal termination of session are major vulnerability of BGP. Simplifying BGP design complexity helps in research, for the root cause analysis of BGP. Deriving technique to prevent the loss of data, reduce the convergence time and maintaining the sessions of BGP by instantly diverting the traffic from teardown / flapped link to the backup link considering as active link. It will be a great success to achieve the goal to maintain the sessions and reduce the BGP convergence time.